1998
DOI: 10.1099/0022-1317-79-1-95
|View full text |Cite
|
Sign up to set email alerts
|

Protein-binding properties of the putative AP-1 and ATF sequences in the feline immunodeficiency virus long terminal repeat.

Abstract: Electrophoresis-mobility-shift assays with nuclear extracts from a feline renal cell line and a Tlymphoblastoid cell line revealed that the AP-1 and ATF sites of feline immunodeficiency virus (FIV) TM2 strain had similar protein-binding properties to those of FIV Petaluma strain and consensus sequences of AP-1 and ATF sites, and that nuclear factors binding to these sites differed between the two cell lines. Cross-competition and gel-supershift assays demonstrated that the AP-1 and ATF sites had similar protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 23 publications
(26 reference statements)
2
8
0
Order By: Relevance
“…Differences were not observed between the expression and replication of mutants encoding both an ATF and AP-1 deletion and those of mutants encoding an ATF deletion only. These findings correlate with those of previous studies that found the ATF response element critical for FIV LTR basal activity, LTR activation by cAMP analogs, and binding of cellular proteins by DNase I footprinting and gel shift assays (17,18,34,37). The importance of the ATFbinding site for virus replication suggests that FIV expression may be at least partially regulated by the ATF/CREB family of transcription factors that bind ATF or cAMP response elements.…”
Section: Fig 4 Replication Of Fiv Ltr Mutant Viruses In Feline Pbmcssupporting
confidence: 80%
See 1 more Smart Citation
“…Differences were not observed between the expression and replication of mutants encoding both an ATF and AP-1 deletion and those of mutants encoding an ATF deletion only. These findings correlate with those of previous studies that found the ATF response element critical for FIV LTR basal activity, LTR activation by cAMP analogs, and binding of cellular proteins by DNase I footprinting and gel shift assays (17,18,34,37). The importance of the ATFbinding site for virus replication suggests that FIV expression may be at least partially regulated by the ATF/CREB family of transcription factors that bind ATF or cAMP response elements.…”
Section: Fig 4 Replication Of Fiv Ltr Mutant Viruses In Feline Pbmcssupporting
confidence: 80%
“…The U3 domain of the FIV LTR has consensus recognition sequences for the cellular transcription factors AP-1, AP-4, ATF (also known as the cyclic AMP [cAMP] response element, or CRE), NF1, and NF-␤ (see reference 20 and references therein and references 25, 28, 30, and 37). Of these putative target sequences, AP-1, AP-4, ATF, and C/EBP recognition sites have been shown to bind cellular proteins by DNase I footprinting and gel shift assays (17,37) and appear to be important for basal promoter activity of the FIV LTR in vitro (22,26,34,37). Furthermore, the AP-1 site is required for T-cell activation responses mediated by protein kinase C, as well as activation by c-Fos.…”
mentioning
confidence: 99%
“…This protein does not bind directly to the FIV LTR but has been suggested to act in conjunction with unidentified cellular transcription factors [79]. The FIV LTR contains known cis -acting elements including binding sites for AP1, AP4, C/EBP, NF1 and ATF [80–83] of which the AP4/AP1 and ATF sites appear to be required for full basal promoter activity [77,8486]. The AP1, C/EBP and ATF motifs have been suggested to co-operate to enhance transcriptional activity in conjunction with OrfA.…”
Section: Transcription and Nuclear Exportmentioning
confidence: 99%
“…Specific competition was accomplished by using a 50-fold molar excess of unlabeled probe. In addition, nonspecific competitors that did not contain the AP-1, ATF, CEBP, or NF-B binding sequence were used to demonstrate specificity and have been described elsewhere (21,25,30). Nuclear extracts for specific and nonspecific competition were derived from 1.…”
Section: Methodsmentioning
confidence: 99%
“…Kawaguchi et al (25) demonstrated by sitespecific mutations that the CEBP site in the FIV LTR is necessary for efficient viral replication in both feline fibroblasts and a T-lymphoblastoid cell line. A number of studies demonstrated that mutations or deletions of both ATF and AP-1 sites resulted in severely reduced basal promoter activity from the FIV LTR and impaired ability of viruses to replicate both in feline lymphocytes and in macrophages (5,21,23).…”
mentioning
confidence: 99%